Pengaruh Struktur Aset, Kepemilikan Manajerial dan Pertum-buhan Penjualan terhadap Kebijakan Hutang di Perusahaan sektor Food and Beverage yang terdaftar di Bursa Efek Indonesia Tahun 2017-2021. - Novita Simamora (Jurnal Akuntansi Nommensen, 2023)
The purpose of this study was to determine asset structure, managerial ownership and sales growth partially and simultaneously affect debt policy in Food and Beverage Sector Companies listed on the Indonesia Stock Exchange in 2017-2021. Source of data in this research is secondary data. This data collection technique is a documentation study. The population used in this study is all financial report data for Food and Beverage Sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample for this research is the financial reports of 10 companies published for the period 2017 to 2021 for a period of 5 years. The data analysis technique used is multiple linear regression analysis. The results showed that partially asset structure, managerial ownership and sales growth had a positive and significant effect on debt policy and simultaneously asset structure, managerial ownership and sales growth had a positive and significant effect on debt policy in Food and Beverage Sector Companies listed on the Stock Exchange Indonesian Securities Year 2017-2021.